Pathways of influence on health-promoting lifestyles in older adults with coronary heart disease: a cross-sectional study - Tian, Zhaoxia; Zhang, Yue; Li, Hongmei; Lv, Xiaochun; Wang, Quanyi; Tian, Weiwei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe global demographic shift toward aging populations has precipitated a significant rise in coronary heart disease (CHD) prevalence among older adults, positioning health promoting lifestyles as a critical component of healthy aging initiatives. Despite increasing recognition of psychosocial factors in chronic disease management, the complex pathways influencing health promoting lifestyles adoption in elderly CHD patients remain insufficiently understood. Current research lacks theoretically grounded investigations examining how cognitive and social determinants interact to shape health behaviors in this vulnerable population.ObjectiveBased on social cognitive theory, this study aims to explore the influencing factors of health-promoting lifestyles in elderly patients with CHD and the path relationships among them.MethodsA cross-sectional study was conducted from a tertiary care hospital. Based on social cognitive theory, the Health Promoting Lifestyle Scale and its related research tools were adopted. Structural equation modeling (SEM) elucidated direct and indirect relationships between variables, supported by correlation analyses and model fit statistics.Results236 eligible elderly patients with CHD participated in this study. Analysis of the results showed that health literacy, perceived social support, and general self-efficacy had a direct positive effect on health-promoting lifestyles, health anxiety has a direct negative effect on health-promoting lifestyles, and perceived social support, self-efficacy, and health anxiety had significant indirect effects on health-promoting lifestyles.ConclusionThis study establishes an social cognitive theory-informed framework where psychosocial resources and cognitive appraisals synergistically influence health behaviors in older adults. The centrality of self-efficacy as a mediator highlights its role in translating environmental supports into sustainable lifestyle changes. Based on the pathway relationships among various factors identified in the study, clinical nursing can construct a comprehensive nursing model. During the nursing process, a comprehensive assessment of the patients’ various indicators should be conducted, and personalized nursing plans should be formulated according to the assessment results. It is necessary to organically integrate aspects such as improving health literacy, strengthening social support, enhancing self-efficacy, and alleviating health anxiety to provide patients with all-round nursing services.